HUBUNGAN SIKAP DAN PRAKTIK DOKTER GIGI PADA PASIEN GERIATRI DI MALANG RAYA - Diwya Nugrahini Hapsari; Kartika Andari Wulan; Yuanita Lely Rachmawati; Nahla (Fakultas Kedokteran Gigi UB, 2023)
ABSTRACT Background: The most common dental and oral problems in the elderly are xerostomia, caries and periodontal disorders. However, treatment and diagnosis in geriatric patients is a challenge because most patients have oral problems accompanied by systemic problems. This matter makes these geriatric patients require special oral health care. Therefore, a dentist must not only have sufficient knowledge but also have good attitudes and skills when providing treatment. Objective: To determine the correlation between the attitude and practice of dentists in geriatric patients in Malang Raya. Methods: Cross-sectional approach using a Google Form distributed through social media. The number of research samples was 265 respondents with snowball sampling technique. Result: Most of the respondents had a fairly good attitude, which was 70.2% and most of the respondents had very good practice criteria, which was 75.8%. Correlative analysis between attitude and practice variables using Spearman test showed p value = 0.123 (p > 0.05). Conclusion: There is no significant correlation between attitude and practice of dentists in geriatric patients in Malang. Keywords: attitude, practice, geriatrics